Satisfaction with residency in Pediatric Surgery in Mexico. Opinion survey results - Carlos Baeza-Herrera; Humberto Velázquez-Pino; Víctor Alarcón-Quezada (Instituto Nacional de Pediatría, 2014)
Much is known with regard to education and conformity of residents of all medical surgical disciplines, particularly since the implementation of the Plan Unico de Especializaciones Médicas. However, for pediatric surgeon little has been investigated. Objective: To evaluate the opinion of recently graduated pediatric surgeons with respect to the institution where they were formed, their teachers, their evaluation processes and themselves. Methods: A questionnaire was given to recently graduated pediatric surgeons in order to obtain information about the institutions where they were trained, their teachers, and evaluations of themselves. Results. Universidad Nacional Autónoma de México and the Instituto Politécnico Nacional had the highest number of graduates the highest college grades average. Slightly over half of them said their training was excellent as residents. However 18 of the total reported that they lacked training in some disciplines. Conclusions. Even with some contradictions, the most valuable finding of the study was the need to promote interchanges with rotations in other institutions.